"O senhor dos anéis : a sociedade do anel" : entre os mitos e as relações de poder/saber - Jesus, Nicaelle Viturino dos Santos de (2016)
Our research object consists of a discursive analysis of filmic materiality "The Lord of the Rings: the ring society" (2001), part of the trilogy (literary / cinematic), the celebrated author J. R. R. Tolkien, under the direction of Peter Jackson. We propose to understand the production of meanings from the examination of the motion picture film, under French guidance Discourse Analysis. Besides the theoretical basis of that area of knowledge, we look at the relations of power, surveillance, control, discipline, according to Foucault's postulates. Then our primary goal is to analyze the (re)actualization of some myths by cinema, a disseminator support ideologies. And as it is a verbal-visual materiality, also have studied the relationship between characters, the environments in which they are, the colors used to compose the scenography, reflecting on the (re)interpretation of the ring as an object of desire, a symbol of power. In order to realize that analysis, we used Orlandi's (1984) proposed, according to which there is a need to circumscribe the object of analysis. In this sense, we made five cuts on the whole discourse: the discourse of / on the myth (the Tower of Babel, the ideal of lost heaven, the Saint Graal), the Christian discourse, the discourse of / about the woman, on the power of surveillance; the nature discourse, in order to build our research corpus. From these cuts, we examine some images (PÊCHEUX, 1999) and discursive sequences. In these terms, the analysis consists of an interrelation between the analytical tool (the cutouts, their (de)superficiality, images, discursive sequences) and a theoretical tool. The last one is based on Barthes (2007), Bernardet (1985), Campbell (1990), Cassirer (1972), Charaudeau (2007), Foucault (1997, 2003, 2007, 2009, 2010, 2011, 2012, 2013), Gregolin (2007), Nazario (2005), Orlandi (1984, 2002, 2012), Pêcheux (1997, 1999), Tressider (2003). As the result of analysis, we observed how values and beliefs are reconstructed, reinterpreted by the cinema. We still emphasize how some situations are (re) placed, providing the inculcation of certain existential human condition (in the fields of religion, nature); constituting a microphysics of power. We note, finally, the movement of the senses, of the discourses.